Cell disruption of Nannochloropsis sp. improves in vitro bioaccessibility of carotenoids and ω3-LC-PUFA. (February 2020) - Bernaerts, Tom M.M.; Verstreken, Heleen; Dejonghe, Céline; Gheysen, Lore; Foubert, Imogen; Grauwet, Tara; Van Loey, Ann M.
Graphical abstract: Highlights: Cell disruption increased carotenoid and ω3-LC-PUFA bioaccessibility. An incomplete lipid digestion was observed for intact Nannochloropsis sp. cells. Carotenoids in Nannochloropsis sp. oil were better incorporated into mixed micelles. High pressure homogenization is effective for enhancing lipid digestibility. Abstract: The incorporation of microalgae into processed food products is considered a sustainable strategy to enrich food products in omega-3 long chain polyunsaturated fatty acids (ω3-LC-PUFA). However, the microstructural properties of the microalgae might influence the nutrient digestibility and bioaccessibility during consumption. The current study proved the importance of cell disruption of Nannochloropsis sp. for the in vitro lipid digestibility and bioaccessibility of ω3-LC-PUFA and carotenoids. While an incomplete lipid digestion and low bioaccessibility values (1–6% for carotenoids and 13% for ω3-LC-PUFA) were observed for untreated biomass, cell disruption by high pressure homogenization resulted in a complete lipid digestibility and a threefold increase in bioaccessibility. It was shown that the Nannochloropsis sp. cell wall and/or cell membrane act as a natural barrier for (lipophilic) nutrients during in vitro digestion. Hence, microalgal cell disruption is a crucial step in the design of healthy food products enriched with microalgae.